Analysis of Junior High School Students’ Errors in Solving Mathematical Literacy Problems based on Newman Procedure Viewed from Students’ Learning Styles (International Journal of Scientific Research and Management (IJSRM), 2024)
This study aimed (1) to determine students’ mathematical literacy skills viewed from learning styles; (2) to know and describe students’ mistakes in solving mathematical literacy questions based on Newman procedure viewed from students’ learning styles; and (3) to know the causes of students’ mistakes in solving mathematical literacy questions based on Newman procedures viewed from learning styles. This research was a qualitative research with a case study type and used a descriptive approach. The subjects of this study were 53 students of class VIII, 11 Public Junior High School, Tegal, Indonesia. The data were collected using questionnaires, tests, and interviews, which were then analysed. The results showed that: (1) the students’ learning styles were visual, auditory, kinesthetic, and auditory-kinesthetic; (2) visual learning style students have the best mathematical literacy skills because they reach the lowest level 3 and the highest level 4, whereas kinesthetic learning style students made the most mistakes; and (3) the causes of students’ errors in solving mathematical literacy questions viewed from their learning styles tend to be the same, i.e.: students do not master patterns and sequence material, and students felt rushed when working on the questions.